Molecular studies of Kappaphycus Doty and Eucheuma J. Agardh: Phylogenetics and DNA barcode assessment / Tan Ji - Tan, Ji (2013)
Kappaphycus and Eucheuma are the main producers of carrageenan worldwide, with stable annual production increments to cater to increasing demands. Extensively used in the food and cosmetics industries, the marketing of carrageenan generates lucrative returns to the industry and economy. The carrageenan industry is one of the key economic sectors in Malaysia, which also offers a means of livelihood to the local community. The extensive morphological variations of Kappaphycus and Eucheuma often resulted in faming of mixed populations which reduced overall carrageenan yields. Molecular taxonomy is thus applied to identify the many locally-named varieties of Kappaphycus and Eucheuma as well as elucidate the phylogeny associated with these red seaweeds. Local varieties, categorized via putative external morphology, were analyzed using the mitochondrial cox2-3 spacer and RuBisCO spacer DNA markers. The cox2-3 spacer provided better phylogenetic delineation compared to the RuBisCO spacer. Results revealed that morphological and color variations are unsupported by genetic data, where many of the local varieties of Kappaphycus and Eucheuma are invalid. Phylogenetics has also shown the genetic distinctiveness of two K. alvarezii genotypes exclusive to Hawaii and Africa that differs from the commonly cultivated K. alvarezii available worldwide. Two genetically different strains of K. striatus were also observed in Malaysia. The local variety Kappaphycus “Aring-aring” displayed unique phenotypic and genotypic traits and may possibly be a new species. E. denticulatum was shown to be dominant in East Malaysian waters, where the “Spinosum” and “Cacing” varieties differ from one another both in terms of morphology and genetics. The “Cacing” variety was shown to be synonymous with E. denticulatum (Burman) Collins & Hervey var. endong Trono & Ganzon-Fortes var. nov. The paraphyletic nature of Eucheuma was also shown and discussed. The usefulness of molecular taxonomy encouraged the assessment of potential molecular markers for DNA barcoding of the rhodophytes Kappaphycus and Eucheuma on a larger scale. Proper establishments of DNA barcode libraries of these commercially important seaweeds would hasten species identifications, phylogenetic inferences, biodiversity studies, population studies, bioinvasion monitoring as well as the identification and selection of superior strains for cultivation. The effectiveness in DNA barcoding of four genetic markers, namely the mitochondrial cox1, cox2, cox2-3 spacer and the plastid rbcL were gauged using a dataset comprised of selected Kappaphycus and Eucheuma samples from Southeast Asia. Marker assessments were performed using established distance and tree-based identification criteria from earlier studies. Barcoding patterns on a larger scale were simulated by empirically testing on the commonly used cox2-3 spacer. The cox2 marker which satisfies the prerequisites of DNA barcodes was found to exhibit moderately high interspecific divergences with no intraspecific variations, thus a promising marker for the DNA barcoding of Kappaphycus and Eucheuma. However, the already extensively used cox2-3 spacer was deemed to be in overall more appropriate as a DNA barcode for these two genera. On a wider scale, cox1 and rbcL were still better DNA barcodes across the rhodophyte taxa when practicality and cost-efficiency were taken into account. The application of DNA barcoding has demonstrated our relatively poor taxonomic comprehension of these seaweeds, thus suggesting more in-depth efforts in taxonomic restructuring.